STRATEGI TIM REDAKSI DALAM MENINGKATKAN KUALITAS PEMBERITAAN PROGRAM DETAK SUMBAR PADANG TV - Laura Ratu Mulia; Oktri Permata Lani (KINEMA: Jurnal Komunikasi dan Penyiaran, 2025)
This study discusses the editorial team's strategies to improve the quality of news coverage in the *Detak Sumbar* program on Padang TV. The main objective is to understand the strategies implemented by the editorial team and to examine editorial aspects from both the editorial and production teams. The research uses a qualitative method with descriptive analysis, and data were collected through observation, interviews, and documentation. The findings show that the *Detak Sumbar* production process has implemented editorial strategies based on seven key points, including maintaining broadcast quality, scriptwriting standards, and obtaining up-to-date and informative news. Additionally, sharing program clips through various digital platforms such as STB, YouTube, Facebook, TikTok, Instagram, and the Padang TV website is also part of the effort to enhance the quality and reach of the news coverage.